2019
DOI: 10.3906/tar-1807-83
|View full text |Cite
|
Sign up to set email alerts
|

Identification of chromosomal regions in the genetic control of quality traits in durum wheat (Triticumturgidum L.) from the Fertile Crescent

Abstract: Durum wheat genetic resources from Turkey and Syria are expected to harbor novel alleles for most traits that are of interest to breeders and consumers. However, there have not been sufficient efforts to investigate the genetic structure of this gene pool. In this study, cultivar Kunduru-1149 (selected from one of the unique landraces, Kunduru) from Anatolia was crossed with a Syrian cultivar, Cham1, to produce recombinant inbred lines (RILs) for quantitative trait locus (QTL) analysis. The RIL population was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The presence of grains with a soft texture can impair pasta quality. In some studies, the variation in vitreousness in durum wheat was in the range of 70-90% (Korkut et al 2007;Alsaleh et al 2019). The percentage of starchy (soft) grains in various Sicilian Rivet accessions ranged from 6 to 72 percent (Spina et al 2023).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of grains with a soft texture can impair pasta quality. In some studies, the variation in vitreousness in durum wheat was in the range of 70-90% (Korkut et al 2007;Alsaleh et al 2019). The percentage of starchy (soft) grains in various Sicilian Rivet accessions ranged from 6 to 72 percent (Spina et al 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Its high protein content makes it suitable for a wide range of end-products of traditional food items (Zingale et al, 2023). Durum wheat accounts for approximately 8% of global wheat production, with the majority (75%) grown in the Mediterranean region, as noted by Alsaleh et al (2019). According to Mulugeta et al (2023), Canada and Türkiye are the largest producers of Durum wheat.…”
Section: Introductionmentioning
confidence: 99%
“…By harnessing the power of molecular markers, such as Simple Sequence Repeats (SSR), durum wheat breeders can develop new cultivars that thrive in diverse environments at higher speeds. Unlike conventional breeding methods, molecular markers enable breeders to quickly and accurately identify plants that exhibit the desired traits (Alsaleh et al, 2019). SSRs are especially useful in detecting genetic variation in individuals (Nadeem et al, 2018) and can be harnessed for genome-wide association studies (GWAS) and marker-assisted selection (MAS), as indicated by Vieira et al (2016).…”
Section: Introductionmentioning
confidence: 99%
“…Gluten proteins (HMW and LMW) determine the quality characteristics of wheat flour. HMW glutenin subunits (GS) are synthesized at the Glu-A1, Glu-B1 and Glu-D1 loci on the long arms of 1A, 1B and 1D chromosomes (HORVAT et al, 2002;ALSALEH et al, 2019). The genes encoding LMW-GS are localized at Glu-A3, Glu-B3 and Glu-D3, which are linked to Gli-1 on the short arm of 1A, 1B and 1D chromosomes (JOHANSSON et al, 2002).…”
Section: Introductionmentioning
confidence: 99%